A Subtitling Analysis Of Directive Utterances In Hugo Movie - Andromeda, Oka, Dra. Dwi Haryanti, M.Hum, Dr. Anam Sutopo, M.Hum (2013)
This research studies about a subtitling analysis of directive utterances in Hugo Movie. The researcher tries to classify the translation shift and the equivalence of subtitling of directive utterances used in Hugo movie. This research belongs to a qualitative research. In collecting the data, the researcher uses the documentation method and technique of coding which can be found in script of subtitling. The data are taken from the subtitling of Hugo Movie. From the collected data, the researcher finds 146 data of the translation shift and equivalence. Based on the result of the data analysis, the researcher finds four the translation shift. From 146 data, there are 127 data or 86. 98% imperative sentences are translated into imperative sentences, 15 data or 10. 27% declarative sentences are translated into declarative sentences, 3 data or 2. 05% declarative sentences are translated into imperative sentences, and 1 data or 0. 68% interrogative sentence is translated into interrogative sentence. Based on the equivalence of subtitling from 146 data of the research, there are 130 data or 89. 05% sentences of utterance which is translated equivalence and the sentence which is translated non equivalence 16 data or 10. 95% sentences. It means that the script of subtitling in Hugo Movie has a good translation.